An Analysis of Ptosis following Subfascial Breast Augmentation: Calculations That Explain Dogma. (16th September 2021) - Brown, Tim
Abstract : Background: Implant placement can improve ptosis due to the position of the nipple, inframammary crease, and base of the breast acting together. The interrelationship between these was quantified via changes in morphometry following subfascial augmentation, and explains the circumstances under which dogma holds true. Methods: One hundred seventy-five patients underwent a series of static measurements before and 3 months after subfascial breast augmentation. Ptosis in the nipple and base of the breast was calculated before and after surgery. Results: All measurements except that of the the lateral sternal margin increased after surgery. All grades of ptosis reduced following surgery. There was lowering of the base in grade 1 patients, but not for other grades. Increased base ptosis correlated with reduced lateral sternal margin (1.9 cm compared with 2.9 cm; left, H 5 = 24.7, p < 0.01; right, H 5 = 24.5, p < 0.01). Implant volume did not correlate with change in ptosis at the nipple or base. Reduced ptosis was associated with implants that are a narrow match of implant to breast (0.52 to 0.95) (left, H 5 = 28.3, p < 0.01; right, H 5 = 24.9, p < 0.01). Decreasing ptosis correlated with lower lateral sternal margin compared to breasts that increased ptosis. Change in ptosis following surgery does not correlate with having children. Conclusions: Subfascial placement has varying effects on ptosis. Non-ptotic or mildly ptotic breasts appear to improve due to a disproportionate descent of the inframammary crease relative to the nipple and base. Patients with little breast tissue are more susceptible to an increase in "bottoming out, " particularly if broad implants are used. A ratio matching implant to the base width has predictive value on outcome. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.